Strategic Information Systems Planning Using the Tozer Methodology: A Comprehensive Literature Review - Alam, Fajar Indra Nur; Tukiman, Tukiman (Department of Informatics Universitas Islam Indonesia, 2026)
The rapid advancement of Information Systems (IS) and Information Technology (IT) has prompted organizations across sectors to adopt systematic approaches for aligning technological initiatives with business strategies. One of the most widely applied frameworks in Indonesia and beyond is the Tozer Methodology for strategic information systems planning. This paper presents a comprehensive literature review of ten selected studies applying the Tozer framework in diverse organizational contexts, including education, telecommunications, publishing, microfinance, trade, media, and interior design services. Through critical synthesis, this review identifies common analytical tools used alongside Tozer (SWOT, PEST, Value Chain, CSF, McFarlan’s Grid, Five Forces), evaluates the effectiveness of the methodology, and highlights recurring challenges such as integration issues, data duplication, and limited scalability. While findings consistently affirm Tozer’s practicality and adaptability, gaps remain in integrating Tozer with emerging technologies such as cloud computing, big data analytics, and artificial intelligence. This review contributes by mapping trends, identifying research gaps, and providing recommendations for future studies and organizational practices aiming to optimize IS/IT strategic alignment.